(1511) The political participation of Egyptian women المشاركة السياسية للمرأة المصرية - Abo EL Nasr, Medhat Mohamed (The Institute of National Planning, 2018)
This paper examines the political participation of women in modern Egypt. The political participation of citizens (male and female) in Egypt is discussed. The purpose of this is to acknowledge the significance of the political environment or context in which women live interact with work through as citizens. An example for the political participation of female social workers is also introduced.